Optimal management strategies for paediatric morphea – insights from a case series - Łagosz, Kinga; Bień, Natalia; Ceryn, Justyna; Barsińska, Paulina; Sobolewska-Sztychny, Dorota; Narbutt, Joanna; Lesiak, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Juvenile localized scleroderma, or morphea, is a rare chronic inflammatory disease primarily affecting the skin and subcutaneous tissue. Treatment options for paediatric cases are diverse, with a lack of standardised guidelines. This case series investigates the efficacy of systemic therapy combining methotrexate (MTX) and oral prednisone in children diagnosed with linear scleroderma. Seven paediatric patients diagnosed with linear scleroderma received systemic treatment consisting of MTX alongside oral prednisone. Clinical evaluation focused on monitoring disease progression and assessing improvements in skin manifestations. All patients demonstrated effective suppression of disease progression and gradual enhancement in skin condition following treatment initiation with MTX e and oral prednisone. This combined systemic therapy shows promising efficacy in halting disease advancement and improving skin manifestations in children with linear scleroderma. These findings underscore the potential benefit of this treatment approach in managing juvenile localised scleroderma; however, further research is necessary to establish comprehensive therapeutic guidelines.